المديونية الخارجية الأردنية وأثرها على الأمن الوطني الأردني خلال الفترة (1990- 2010 ) (المجلة العراقية للعلوم الاقتصادية, 2018)
This study aims to identify the evolution of Jordan's external debt in various forms in terms of the outstanding balance outstanding during the period (1990-2010) and study the strategies adopted by successive Jordanian governments in the management of debt and examine the effects of foreign debt of Jordan on the Jordan National manna that the indebtedness of the most important problems faced by developing countries in general and LDCs in particular, given the dimensions of negative effects on the economic development process in these countries, threats to the stability of its financial system , and that will fall on the case of Jordan as one of the developing countries will begin this study by the hypothesis of a negative relationship between the size of the external debt of Jordan and all of: the level of stability, security and military, the level of economic stability, and the level of social stability. The importance of this study to shed light on the foreign debt of Jordan in light of the fact that the scarcity of literature and studies on the external debt of Jordan and the impact of this debt on the national security of Jordan, and reach conclusions that lead us to make recommendations and appropriate solutions at the end of the study in this regard to the decision-maker and open new horizons for researchers to expand the study of this phenomenon. . Through the assistance of all the researcher can get it from books, periodicals, magazines, reports and previous studies, in addition to search engines over the internet. The study concluded that the signs of the debt crisis of Jordan has appeared in the late eighties of the twentieth century, through excessive successive Jordanian governments to rely on loans Alkhtareign in project finance and capacity strengthening defense and security, which led to erosion of the pillars of national security in all its dimensions, and threaten the security and stability Jordanian state, so the researcher recommends that the decision maker's economic and political Jordanian search for new alternatives is borrowing through the establishment of investment projects and production, development and reduce the recourse to external funding sources, and the fight against corruption in all its forms through tighter oversight and enforcement of laws and legislation deterrent